Effect of flavonol on reduction of acrylamide in Maillard reaction and its correlation with antioxidant capacity - CHENG Jun; REN Yiping; ZHANG Ying; ZHANG Yu (浙江大学学报. 农业与生命科学版)
In 2002, the discovery of acrylamide contaminant in heat processing foods got a worldwide attention because of its genetic and reproductive toxicities as well as mutagenic and carcinogenic properties. Therefore, it is necessary to find effective additive agents to reduce the formation of acrylamide in Maillard reaction.We investigated the effects of flavonols on the reduction of acrylamide in an equimolar asparagine-glucose Maillard reaction system using potato matrix and microwave heating. To investigate the dose-response effect, six different levels of flavonols were added into the self-prepared Maillard reaction system and different levels of acrylamide were generated and observed. Meanwhile, the correlation between the inhibitory rate of acrylamide affected by flavonols and the change of Trolox equivalent antioxidant capacity (Δ TEAC) in Maillard reaction products was also evaluated. Acrylamide levels in Maillard reaction products were determined by ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS) and quantified with multiple reaction monitoring (MRM) mode after the pretreatment of final products. Δ TEAC values were simultaneously measured by three representative antioxidant evaluation methods, i.e. DPPH (1, 1-diphenyl-2- picrylhydrazyl), ABTS (2, 2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) and FRAP (ferric reducing ability of plasma).The results indicated a non-linear relationship between addition levels of flavonols and inhibitory rate of acrylamide. The optimal addition level of all six flavonols, i.e. kaempferol, kaempferol-3-o-glucoside, quercetin, quercetin-3-o-glucoside, myricetin and rutin was 1×10-9 mol/L, which exerted their maximal inhibitory effect against the generation of acrylamide. The inhibitory rate ranged from 48.9% to 69.3% when different types of flavonols were used at the optimal addition level. Taking Δ TEAC as the antioxidant measurement index, the correlation coefficients between Δ TEAC determined by three different antioxidant evaluation methods (DPPH, ABTS and FRAP) and inhibitory rate of acrylamide were 0.885 3, 0.834 2 and 0.805 3 respectively, indicating a close correlation between the inhibitory effects of flavonols against the generation of acrylamide and the antioxidant capacity in Maillard reaction products.Based on microwave heating and Maillard reaction system, this study not only describes novel experimental system for investigating the inhibitory effect of phytochemicals (e. g. flavonols) against the generation of acrylamide, but also provides substantial evidence of the correlation between the inhibitory rate of acrylamide and antioxidant capacity in Maillard reaction products.